Price Discovery, Causality and Volatility Spillovers in European Union Allowances Phase II: A High Frequency Analysis - Daniel Rittler (University of Heidelberg, Department of Economics, 2009)
This paper deals with the modeling of the relationship of European Union Allowance spot- and futures-prices within the second commitment period of the European Union Emission Trading Scheme. Based on high frequency data, we analyze causality in the first and the second conditional moments. To reveal long run price discovery we compute the common factor weights proposed by Schwarz and Szakmary (1994) and the information share proposed by Hasbrouck (1995) based on the estimated coefficients of a vector error correction model. To analyze the short run dynamics we perform Granger causalty tests. The GARCH-BEKK model introduced by Engle and Kroner (1995) is employed to analyze the volatility transmission structure. We identify the futures market to be the leader of the long run price discovery process whereas a bidirectional short run causality structure is observed. Furthermore we detect unidirectional volatility transmission from the futures to the spot market at highest frequencies.
urn:nbn:de:bsz:16-opus-100948
Keywords: 330; CO2 Emission Allowances; Causality; Volatility Transmission; Spot Prices; Futures Prices; Emissionshandel; Preis; Volatilität; Emissionshandel; Derivat; Schätzung; EU-Staaten